Patrimônio cultural e informação: a Renda Irlandesa de Divina Pastora e suas conexões com a República da Irlanda - Silva, Carlos Henrique Paes dos Santos (2024)
Cultural Heritage, like Information Science, is an evolving interdisciplinary scientific field that is consolidated with each study conducted from both perspectives. Thus, tangible and intangible cultural heritage can be studied from the perspective of Information Science, given the informational load and knowledge it carries, as well as the informational phenomena it triggers. In this context, the present study investigates Irish Lace from the city of Divina Pastora in the state of Sergipe, which has been recognized by IPHAN as Intangible Cultural Heritage of Brazil since 2009, in the light of Information Science. In order to obtain answers to the questions that drive this study: What did foreign literature have to contribute to the scientific discussion on Irish Lace? What are the existing international sources of information and where are they located? What were the informational and social processes that brought this information and knowledge about lace to the city of Divina Pastora? What are the similarities between the Irish lace of Divina Pastora and that produced in Ireland? Thus, the general objective of this research is to analyze the contributions of foreign literature on Irish lace, identifying international sources of information, the informational and social processes that enabled the circulation of this knowledge to the city of Divina Pastora, as well as the similarities between Irish lace produced in Ireland and that made in Divina Pastora/SE. Thus, to achieve this objective, the following specific objectives were established: to identify the types of Irish lace produced in the Republic of Ireland; to produce a documentary video presenting a comparative study between the lace produced in the Republic of Ireland and that produced in Divina Pastora/SE, thus identifying the similarities between them; to identify foreign sources of information dealing with Irish lace; understand how Information Science can contribute to the study of Cultural Heritage, understanding it as a source of information, and understand the process of information circulation through the production of Irish Lace. The research is characterized as descriptive, exploratory, and bibliographic, using bibliographic and documentary surveys as data collection instruments, which were discussed and analyzed according to Bardin's Content Analysis. The results of this study show that there are similarities between the Irish Lace of Divina Pastora and those produced in Ireland, and also points out those that use the same technique, materials, and design to be constituted. In addition to presenting the factors that contributed to the circulation of information about Irish Lace, from here to Ireland, and the process of reframing this information in the city of Divina Pastora. The technical product of this dissertation was a documentary video that presents the results of this study and can be used by the lace-making associations of Divina Pastora as a tool for mediating information about Irish lace to users who use these spaces to access and retrieve cultural information. However, it should be noted that Cultural Heritage translates into information that circulates and is retrieved, accessed, mediated, appropriated, and reinterpreted to construct new knowledge and practices.